A training program to provide secondary school students with the skills of plant ornamentation (Journal of the College of Basic Education, 2022)
The most important thing that distinguishes a person is his ability to use his hands to be distinguished and effective in his field of specialization and prestigious among the members of his society, so researchers and educators always seek a serious attempt to acquire and develop students’ skills of all kinds in order to employ the capabilities and skills of students in several fields, for this reason the researcher conducted a study An exploratory survey on the reality of the level of skills education in secondary schools, and found a discrepancy in the level of interest of male and female teachers to teach these skills to students, especially the skills of botanical ornamentation, which are almost non-existent.